Right man com bossa: as representações do Brasil e do American way of life nas propagandas comerciais em revistas brasileiras de variedades (1937-1947) - Marina Helena Meira Carvalho (2015)
This essay analyses the representations of Brazil and American way of life in advertisements in Brazilian magazines between 1937 and 1947. These advertisements gained national importance with the Estado Novo. They gained international importance, as well. The project named Cooperation with US Advertisers in the other American Republic (that was created by the Office of Coordinator of Inter-American Affairs), interested in this work, and the rise of the Nazi-fascist regimes are exemples of this importance. The national theme and the relationship between Brazil and the United States were themes present in advertising representations, both in articles and in advertisements. Thus, advertisers became historical actors that consolidate and resignify imaginaries beyond them, such as Pan-Americanism, patriotism and nationalism. Therefore, we also consider advertisement a place for political discussion. In addition, we analyze the relations established by the advertising field in both: Estado Novo and Good Neighbor Policy, in the space between negotiations and conflicts. We problematize, then, identifications and differences built by advertisers in the representations of Brazil and the American way of life in advertisings present in three Brazilian magazines (Fon-Fon, A Cigarra e O Cruzeiro) and in two of advertising field (Publicidade e Anuário de Publicidade).